What is The Effectiveness of Virtual Reality Interventions On Upper Limb Motor Function Recovery In Stroke Survivors? : A Comprehensive Systematic Review - Vania Florencia Susanto; Stella Vaniadewi (The Indonesian Journal of General Medicine, 2026)
Background: Stroke is a leading cause of long-term disability worldwide, with upper limb motor deficits affecting up to 85% of survivors and significantly impairing functional independence. Virtual reality (VR) has emerged as a promising technology for neurorehabilitation, offering task-specific, intensive, and engaging therapy. Methods: This systematic review synthesized evidence from 80 sources including randomized controlled trials (RCTs), etc examining VR interventions for upper limb recovery in stroke survivors. Primary outcomes included upper limb motor function measured by Fugl-Meyer Assessment Upper Extremity (FMA-UE), Action Research Arm Test (ARAT), Box and Block Test (BBT), and activities of daily living (ADL). Results: Pooled meta-analyses demonstrated significant positive effects favoring VR over conventional therapy for upper limb function (SMD 0.20-0.63; moderate certainty evidence). The largest benefits occurred when VR was added to usual care (SMD 0.42, 95% CI 0.26-0.58) rather than replacing conventional therapy (SMD 0.20, 95% CI 0.12-0.28). Subacute stroke patients (1-6 months) showed the greatest ADL gains (SMD 0.52), while acute phase (<1 month) effects were non-significant (SMD 0.22). Immersive VR produced larger effects on FMA-UE (MD 6.33, 95% CI 4.15-8.50) compared to non-immersive systems. Dose-response analysis revealed interventions exceeding 15 total hours yielded superior outcomes (MD 9.67, 95% CI 4.19-15.15). Discussion: The therapeutic efficacy of VR is maximized in subacute stroke patients with moderate-to-severe impairment when delivered as an adjunct to conventional therapy for >15 hours over >4 weeks. Purpose-built rehabilitation VR systems demonstrate superiority over commercial gaming systems. Adverse events were minimal and transient. Conclusion: VR interventions are effective and safe for upper limb motor recovery in stroke survivors, with optimal benefits in subacute patients receiving sufficient dosing as an adjunctive therapy.